Using of recycled clay brick/fine soil to produce sodium hydroxide alkali activated mortars. Issue 13 (October 2021) - Alzeebaree, Radhwan; Mawlod, Arass Omer; Mohammedameen, Alaa; Niş, Anıl
In the study, the recycled clay brick powder/fine soil powder-based sodium hydroxide alkali-activated mortar (AAM) specimens were prepared by mixing different percentages (100/0, 80/20, 60/40, 40/60, 20/80, and 100/0, respectively) to investigate the mechanical and durability performance of sustainable AAM specimens for the possible utilization instead of OPC. The constant ratio of glass powder was used in the production of AAM to increase the alkalinity and improve the mechanical properties of alkali-activated mortar. Also, the influences of sodium hydroxide molarity concentrations (8, 10, 12, 14, and 16 M) on the performance of AAM specimens were studied. The compressive strength, water absorption, and water sorptivity tests were conducted on the AAM specimens and the relationships between the investigated parameters were analyzed. The obtained results revealed that the fine soil powder replacement with clay brick powder improved the compressive strength, and reduced water absorption and water sorptivity up to 80% replacement ratios, and the superior mechanical and durability performance was obtained in the 80% fine soil powder-based AAM specimens. For the higher fine soil powder replacement ratio (100%), the performances of the AAM specimens were found to be adversely affected. Besides, the concentration of NaOH solution significantly influenced the material performances of the fine soil powder-based AAMs and 12 M NaOH concentration performed superior mechanical and durability performance. The strength enhancement of the AAMs was found to be significant after 90 days of ambient curing period.